Green and efficient removal of toxic lead and chromium from synthetic leather tannery wastewater using electrocoagulation - Arshad Iqbal Jarwar,; Khadija Qureshi,; Imran Nazir Unar,; Zulfiqar Ali Bhatti, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Most of leather tanneries in Pakistan dispose of tannery effluent untreated in sewage lines causing serious harmful environmental impact. Some of tanneries use conventional activated sludge process releasing large quantity of sludge and not effective for treating heavy metal in leather tanneries. The manuscript deals with implementation of electrocoagulation technology for removal of Cr and Pb from Leather tannery effluent, investigation of operating parameters current density, treatment time and pH on removal efficiency. Electrodes was made of Iron having dimension 9.5 cm x 0.6 cm x 0.4 cm and affective surface area of electrode was 76 cm2 . After conducting different experiments at various operating conditions, pH 3.5 and current density 18.8 milliamp/cm2 was found to be optimized condition for treating 1 liter of synthetic leather tannery effluent. The maximum removal efficiency of chromium and lead was obtained 87.8 % and 62.7 % respectively at pH 3.5 and current density of 18.8 milliamp/cm2 . The EDX analysis of sludge shows presence of chromium, lead and iron element in sludge and FTIR analysis shows the presence of hydroxyl functional group in sludge, it is strong evidence of iron polymer complexes formation with chromium and lead during treatment of synthetic leather tannery wastewater. Both of these analysis show strong evidence of effective electrocoagulation process. It was proved that electrocoagulation can effectively treat synthetic leather tannery effluent. The SEM analysis shows production of coagulant on surface of electrode.